PERCEPTION BUILDING OF PAKISTANI WOMEN’S ROLE IN “SUCCESSFUL MARRIAGES” AS CONSTRUCTED BY PAKISTANI TELEVISION DRAMAS: A SPEECH ACT THEORY ANALYSIS - Gul Rukh; Dr. Mubashir Ahmad (International Journal of Contemporary Issues in Social Sciences, 2024)
This study looks at the portrayal of women's roles and the changing dynamics of women's empowerment within marriage in Pakistani society, as seen in the TV dramas "Durr e Shahwar" (2012) and "Mannat Murad" (2023). It investigates how these dramas reflect changing cultural ideals and gender roles, as well as how the media influences attitudes and behaviors. The study employs Speech Act Theory to qualitatively examine the power of language in generating narratives through locutionary, illocutionary, and perlocutionary acts, exposing how television impacts society norms and conceptions of women's empowerment.